Educational Approaches to Cultivating Environmental Consciousness among Higher Education Students in Ukraine - Kyseliuk, Nataliia; Martyniuk, Alla; Hubina, Alla; Alyieva, Alvina; Litkovych, Yuliia; Tryndiuk, Vflentyna (Grassroots Institute, 2024)
In the face of escalating environmental challenges such as climate change, resource depletion, and biodiversity loss, higher education institutions (HEIs) play a critical role in fostering environmental consciousness among future professionals. The research aims to analyze current pedagogical strategies, examine innovative development and digitalization factors, and explore how higher education can promote sustainable environmental consciousness among graduates. A combination of complementary methods, including analysis, synthesis and abstraction were used. The essential structural elements of the system of ecological consciousness, as well as the criteria and indicators of its formation, are also defined. Results revealed that the main prerequisites for low environmental awareness among students of higher education institutions in Ukraine are the insufficient development of civil society institutions, lack of motivation to comply with environmental legislation, and an inadequate level of public awareness of sustainable development and environmental stewardship priorities. Environmental education in higher education is often delivered in a traditionally minimalist format, with a narrow sectorial focus that fails to adequately foster environmental awareness development among future professionals. An innovative vision of the pedagogical strategy for forming environmental awareness of students of higher education institutions through fundamental life values, attitudes towards the intrinsic value of nature, and society's responsibility for their conservation and sustainable development is proposed.
Keywords: Environmental awareness; Environmental communication; Emotional intelligence; Communication ethics; Methods of forming